Cytotoxic Effect of the Red Beetroot (Beta vulgaris L.) Extract Compared to Doxorubicin (Adriamycin) in the Human Prostate (PC-3) and Breast (MCF-7) Cancer Cell Lines - J. Kapadia, Govind; A. Azuine, Magnus; Subba Rao, G.; Arai, Takanari; Iida, Akira; Tokuda, Harukuni (Anti-Cancer Agents in Medicinal Chemistry, 2011)
Previous cancer chemoprevention studies from our laboratories and by other investigators have demonstrated that the extract of red beetroot (Beta vulgaris L.), the FDA approved red food color E162, can be effective in suppressing the development of multiorgan tumors in experimental animals. To further explore this finding, we have compared the cytotoxic effect of the red beetroot extract with anticancer drug, doxorubicin (adriamycin) in the androgen-independent human prostate cancer cells (PC-3) and in the wellestablished estrogen receptor-positive human breast cancer cells (MCF-7). This red colored anticancer antibiotic was selected for comparative cytotoxic study because its chemical structure with a planar configuration of an aromatic chromophore attached to a sugar molecule is remarkably similar to that of betanin, the beetroot extract constituent primarily responsible for its red color. Both doxorubicin and the beetroot extract exhibited a dose-dependent cytotoxic effect in the two cancer cell lines tested. Although the cytotoxicity of the beetroot extract was significantly lower when compared to doxorubicin, it continued to decrease the growth rate of the PC-3 cells (3.7% in 3 days vs. 12.5% in 7 days) when tested at the concentration of 29 μg/ml. In contrast, doxorubicin, at the same concentration level, completely inhibited the growth of the PC-3 cells in three days. Similarly, comparative studies in the normal human skin FC and liver HC cell lines showed that the beetroot extract had significantly lower cytotoxic effect than doxorubicin (8.6% vs. 100%, respectively, at 29 μg/ml concentration of each, three-day test period). The results suggest that betanin, the major betacyanin constituent, may play an important role in the cytotoxicity exhibited by the red beetroot extract. Further studies are needed to evaluate the chemopreventive potentials of the beetroot extract when used alone or in combination with doxorubicin to mitigate the toxic side-effects of the latter.
Keywords: erythema